Davčno obravnavanje trikotnih in verižnih poslov v sistemu DDV na področju mednarodne trgovine - Pozvek, Maruša (visokošolska dela, 2019)
Establishment of internal market, is primarly reason for the introduction of the institution of tripartite transactions. Free movement of goods is one of the freedoms of the single market of the EU, that allows successive sale of goods from the first seller to the last buyer, which is concluded between three taxpayers each from different country.Tripartite transaction (quasi and genuine ) are subtype of the chain transaction. When taxpayers are each form different country of the EU, we are talking about genuine triangular transactions, for which we use simplification in order to facilitates the movement of goods within the EU and reduce administrative obligations. Triangular transactions are the most demanding fields, in terms of tax treatment. Especially problematic are quasitriangular transactions in which one link in the chain is a natural person, a company that is one of the links in the chain is established outside the EU, or when the goods travel from the first country to second and then to third country. In the quasi-triangular transactions for a combination of intra-EU exports and imports of goods is required appropriate tax analysis, because the simplifications does not apply for those transaction, so tax solutions vary from case to case. In practice, the participants in the business often abuse the VAT identification numbers for unlawful purposes, such as various fraud and tax evasion. In the field of international business VAT system requires a lot of attention to the law applicable in another country or Member State or third country. Complex terms and unclear definitions in the VAT directive are leaving too much room in decision-making process in front of national tax authorities, which are mandatory for the taxpayers. So, if national authorities have different interpretations of the same institute and are using the same measures in a different way, that can lead to violations of the taxpayers rights. Differences in approach can lead to serious problems such as double taxation or no taxation at all. This creates legal uncertainty and causes unnecessary material costs for companies doing business across the EU and the world. VAT system and international trade are closely linked to trade Incoterms, because with the inclusion of one of the Incoterms in the sales contract the parties clearly and unequivocally agree on when it is considered that the seller has fulfilled its obligation to supply the goods. In VAT system repeatedly comes to conflicts between taxpayers involved in transactions because each link in the chain has to prove that it has fulfilled its tax obligations.
Keywords: blago; davčna obveznost; davčne obveznosti; davčni sistemi; davek na dodano vrednost; disertacije; dobava; ID številka za DDV; izvoz; mednarodna trgovina; pridobitev; trgovinske klavzule Incoterms; tristranski posel; uvoz; verižni posel